2010
DOI: 10.1038/hr.2010.110
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure variability in relation to outcome in the International Database of Ambulatory blood pressure in relation to Cardiovascular Outcome

Abstract: Ambulatory blood pressure (BP) monitoring provides information not only on the BP level but also on the diurnal changes in BP.In the present review, we summarized the main findings of the International Database on Ambulatory BP in relation to Cardiovascular Outcome (IDACO) with regard to risk stratification based on BP variability. The predictive accuracy of daytime and nighttime BP and the night-to-day BP ratio depended on the disease outcome under study and treatment status, and differed for fatal outcomes c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0
15

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 54 publications
3
46
0
15
Order By: Relevance
“…Schillaci et al 38 and Roman et al 43 also observed this lack of association in Caucasians with essential hypertension. Contradictory results have been provided over the years regarding the predictive value of BP variability, 4,8,10,14 which might be due to differences in methods, too few events or different indexes of BP variability. Interestingly, most of these studies focused on the general population or hypertensive groups, excluding the possibility that BP variability might be an effective measurement for the early identification of those at risk when focusing on normotensive groups exclusively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Schillaci et al 38 and Roman et al 43 also observed this lack of association in Caucasians with essential hypertension. Contradictory results have been provided over the years regarding the predictive value of BP variability, 4,8,10,14 which might be due to differences in methods, too few events or different indexes of BP variability. Interestingly, most of these studies focused on the general population or hypertensive groups, excluding the possibility that BP variability might be an effective measurement for the early identification of those at risk when focusing on normotensive groups exclusively.…”
Section: Discussionmentioning
confidence: 99%
“…50 Nonetheless, the weighted SD dn technique used in the present study was suggested as an accurate and useful measure. 4,10 Lastly, echocardiography was not used for determination of left ventricular mass, but we used a validated electrocardiographic method (Cornell product).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 BP is a highly variable physiological trait, the fluctuation of which is a complex interaction between external environmental stimuli and the responses of individual cardiovascular systems. [3][4][5][6][7] From the view point of clinical management, BP variability consists of at least two types of phenomena: longterm fluctuations, such as day-night, day-today, weekly (for example, Monday BP surge) and seasonal changes, and short-term BP variations that occur within the daytime and nighttime periods (Figure 1). Several studies, but not all, have demonstrated that both short-term BP variability and long-term BP variability themselves are significantly associated with the target-organ damage and with future cardiovascular events independently of the 24-h BP levels.…”
mentioning
confidence: 99%
“…Several studies, but not all, have demonstrated that both short-term BP variability and long-term BP variability themselves are significantly associated with the target-organ damage and with future cardiovascular events independently of the 24-h BP levels. [3][4][5][6][7] Intriguingly, certain reports have suggested that the peak of the incidence of cardiovascular diseases (CVDs) is likely to parallel the time with a greater extent of the BP variations. 1,8,9 For example, with respect to diurnal variation, most studies have shown an increased incidence of acute myocardial infarction, sudden cardiac death and stroke during the morning periods after waking up, and this variation appears to be closely associated with the diurnal variation of BP (that is, morning BP increase).…”
mentioning
confidence: 99%